PENELUSURAN PERILAKU METAKOGNITIF MAHASISWA DALAM PEMECAHAN MASALAH MATEMATIKA - Dona Afriyani (Ta'dib, 2011)
This article describes self-belief and intuition, and knowledge about students’ thinking process in solving problems. This research employed qualitative approach using quantitative method. Techniques of data analysis were data reduction, data display and conclusion. The finding showed that: 1) students of high group had possessed self-belief and intuition, and knowledge about students’ thinking process in solving problems, but had not possessed conditional knowledge yet. 2) Students of average group had possessed good self-belief, but had not intuition and knowledge about students’ thinking process in solving problems yet. 3) Students of low group had not possessed the above mentioned two metacognitive behaviors in solving problems yet.Kata kunci: metakognitif, masalah matematika